Plasticizer exposure of infants during cardiac surgery - Eckert, Elisabeth; Müller, Johannes; Höllerer, Christine; Purbojo, Ariawan; Cesnjevar, Robert; Göen, Thomas; Münch, Frank (Toxicology Letters, 2020)
In the present study we investigated the internal exposure situation of infant patients to the plasticizers TEHTM (tri-2-ethylhexyl trimellitate) and DEHP (di-2-ethylhexyl phthalate). The study collective included 21 infant patients aged 2–22 months that had to undergo cardiac surgery using cardio pulmonary bypass (CPB). Each patient, but one, received blood products during surgery. A special feature was that the used CPB tubings were exclusively plasticized with the alternative plasticizer TEHTM and were free of the standard plasticizer DEHP, that raises increasing toxicological concern. The blood products were stored in DEHP plasticized blood bags. Blood and urine samples of each infant patient were analysed before and after the surgery for the levels of the plasticizers DEHP and TEHTM and their metabolites. In general, the plasticizers were detected in the post-surgery blood samples only, with TEHTM in low levels (median 18.4 μg/L) and DEHP in rather elevated levels (median 1046 μg/L). With respect to the urine samples, TEHTM metabolites were not detected in any of the samples. DEHP metabolites were found in all urine samples, however, in significantly increased median levels in the post-surgery urine samples of the infants (increase factor 5–26). Thus, the present study clearly demonstrates the strong contribution of standard medical procedures to the internal plasticizer burden of patients. Particularly with regard to the suspected endocrine disrupting activities of the phthalate plasticizer DEHP, the elevated internal levels of this plasticizer and its metabolites in infants following cardiac surgery are alarming.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Biomonitoring; Cardio pulmonary bypass; DEHP; Medical devices; Packed red blood cells; TOTM; Urine